LITERACY MOVEMENT-BASED ISLAMIC EDUCATION LEARNING MANAGEMENT (CASE STUDY AT UPTD SMPN 1 SINDANG, INDRAMAYU REGENCY) - Mohamad Fachrur Rozi (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Developments have demanded the world of education to be able to adapt quickly where all information can be obtained. Literacy is one of the foundations that has now become a necessity in teaching and learning activities as a source of finding references, identifying, accessing, evaluating, and incorporating information in teaching and learning activities. The ease of accessing various information needs to be addressed carefully by an educator by increasing digital literacy competencies to create a society with critical and creative mindsets and views. For this reason, digital literacy development management is an indicator of achievement in the field of education. This study aims to (1) find out how literacy is in learning Islamic religious education at UPTD SMPN 1 Sindang (2) to analyze and describe understandings of management of increasing literacy skills in learning Islamic religious education at UPTD SMPN 1 Sindang (3) to find out the supporting factors and obstacles to management of increasing literacy in learning Islamic religious education at UPTD SMPN 1 Sindang. This study uses a qualitative approach that is descriptive in nature to describe the UPTD SMPN 1 Sindang, Indramayu Regency to increase literacy competence in learning Islamic religious education. In collecting data, researchers used observation, interview and documentation methods. Meanwhile the guarantor of the validity of the data uses the process of data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) Literacy in learning Islamic religious education, among other things, is to improve learning, to access information and search for information from it, is used as a means of communication in delivering learning material, is used to evaluate and filter various sources of information in learning . (2) UPTD SMPN 1 Sindang, Indramayu Regency, increasing literacy in learning Islamic religious education at UPTD SMPN 1 Sindang, Indramayu Regency includes strengthening character and responsibility in using media as a learning tool, providing an understanding of the importance of literacy by preparing a variety of reading sources, habituation to reading and use the media in the teaching and learning process.